1994
DOI: 10.1056/nejm199406163302403
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of Tuberculosis in New York City -- An Analysis by DNA Fingerprinting and Conventional Epidemiologic Methods

Abstract: In the inner-city community we studied, recently transmitted tuberculosis accounts for approximately 40 percent of the incident cases and almost two thirds of drug-resistant cases. Recent transmission of tuberculosis, and not only reactivation of latent disease, contributes substantially to the increase in tuberculosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
383
11
11

Year Published

1995
1995
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 711 publications
(439 citation statements)
references
References 16 publications
34
383
11
11
Order By: Relevance
“…However, this did not reach significance at the P l 0n05 level and should be treated with caution, especially in view of the use of multiple significance testing in this study. Increased clustering among HIVinfected tuberculosis patients has been found in some studies [7,8] but not in others [6,9]. High levels of clustering in HIV infected patients are likely to reflect problems with nosocomial transmission of disease [10].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, this did not reach significance at the P l 0n05 level and should be treated with caution, especially in view of the use of multiple significance testing in this study. Increased clustering among HIVinfected tuberculosis patients has been found in some studies [7,8] but not in others [6,9]. High levels of clustering in HIV infected patients are likely to reflect problems with nosocomial transmission of disease [10].…”
Section: Discussionmentioning
confidence: 95%
“…The high degree of heterogeneity means indistinguishable strains are likely to represent chains of recent transmission [5]. This property has been exploited in a number of studies of tuberculosis transmission in different settings [6][7][8][9][10]. However, the time required to culture sufficient M. tuberculosis for DNA extraction delays the public health benefits of molecular epidemiological techniques.…”
Section: Introductionmentioning
confidence: 99%
“…During the 1980's, it was believed in the industrialized countries that the eradication of tuberculosis (TB) was imminent, and research in this field became scarce. Only in the early 1990's, when outbreaks of multidrugresistant tuberculosis (MDR-TB) in HIV-positive subjects in the USA and Europe were published, worldwide attention was given to the problem (3) . MDR-TB is defined as a case with a bacillus resistant to at least RFP + INH (4) .…”
Section: Introductionmentioning
confidence: 99%
“…Population based studies in different developed countries demonstrated that tuberculosis resulting from recent transmission was higher than the estimated 10% predicted by traditional epidemiological studies. In these countries, 25% to 45% of new cases of tuberculosis were demonstrated to be the result of recent transmission (8,62,63). A common denominator of risk factors was found to be associated with recent transmission: lower socioeconomic status and HIV coinfection.…”
Section: Transmission and Tuberculosis Controlmentioning
confidence: 99%